Three-dimensional electro-catalysis modified particle electrode based on sol-gel method as well as preparation method and application of three-dimensional electro-catalysis modified particle electrode

By doping Ce, Sn, and Sb active components on coconut shell activated carbon, three-dimensional electrocatalytic modified particle electrodes were prepared, which solved the problem of inefficiency in traditional two-dimensional electrochemical systems when dealing with difficult degradation of organic matter, and achieved more efficient wastewater treatment and stronger electrocatalytic oxidation capabilities.

CN119735270AActive Publication Date: 2025-04-01CHINA ENERGY ENG CORP LTD +2

Patent Information

Application Number
CN202411940590.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

When treating difficult-to-degrade organic matter in wastewater, traditional two-dimensional electrochemical systems have problems such as small space-time yield, limited mass transfer, low current efficiency, and low area-to-volume ratio. The electrical conductivity of activated carbon particles is insufficient, resulting in poor electrochemical oxidation capacity.

Method used

The active components of Ce, Sn, and Sb were doped into coconut shell activated carbon by sol-gel method, and a three-dimensional electrocatalytic modified particle electrode was prepared, which improved the activity and conductivity of the particulate activated carbon.

Benefits of technology

It significantly improves the degradation performance of difficult-to-degrade organic matter in wastewater, enhances the feasibility of engineering application of particulate electrodes, and improves the treatment efficiency of pollutants in high-salt wastewater.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119735270A_ABST
    Figure CN119735270A_ABST
Patent Text Reader

Abstract

The invention relates to a three-dimensional electro-catalysis modified particle electrode based on a sol-gel method and a preparation method and application thereof, and relates to the technical field of water pollution treatment in environmental protection, the preparation method comprises the following steps: (1) pretreating coconut shell activated carbon particles to obtain pretreated coconut shell activated carbon particles; (2) uniformly mixing stannic chloride, antimony chloride, cerous nitrate, a hydrolytic polycondensation catalyst and a solvent to obtain a mixed solution; and (3) putting the pretreated coconut shell activated carbon particles into a mixed solution, carrying out heating treatment, taking out the coconut shell activated carbon particles, and sequentially drying and calcining the coconut shell activated carbon particles to obtain the three-dimensional electro-catalysis modified particle electrode. According to the three-dimensional electrode filler for electro-catalysis, coconut shell activated carbon particles serve as a carrier, and cerium, tin, antimony and other active components are loaded on the activated carbon particles through a sol-gel method to achieve modification of a particle electrode in a three-dimensional electro-catalysis system. The method is high in catalytic oxidation efficiency and good in stability, and has good application prospects in electrochemical treatment of non-biodegradable organic wastewater and high-salinity wastewater treatment processes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water pollution treatment, and in particular to a three-dimensional electrocatalytic modified particle electrode based on a sol-gel method, and a preparation method and application thereof. Background Art

[0002] Electrochemical advanced oxidation processes (EAOPs) are highly efficient, mild, easy to operate, and environmentally compatible in converting and degrading refractory organic matter in solution. EAOPs have attracted increasing attention due to their ability to generate reactive oxygen species that can convert organic pollutants into smaller molecular components or achieve mineralization. In particular, in recent years, three-dimensional electrocatalysis has solved some of the problems encountered by traditional two-dimensional electrochemical systems, such as low time-space yield, mass transfer limitations, low current efficiency, and low area-to-volume ratio. In a three-dimensional electrocatalytic system, particle electrodes serve as the third electrode to form multiple microelectrochemical cell reactors under the action of an electric field. During the three-dimensional electrolysis process, both the anode and particle electrodes can produce strong hydroxyl radical oxidants (·OH) for chemical reactions, thereby increasing the electrochemical reaction rate and improving the degradation rate of organic pollutants. Therefore, three-dimensional electrode technology has received increasing attention in recent years.

[0003] Particle electrodes are generally considered to be the key to the electrocatalytic oxidation performance in three-dimensional electrocatalytic systems. In addition, by comparing various particle electrode materials, it is found that the specific surface area of ​​carbon-based materials is significantly higher than that of metal-based materials. Activated carbon is the most commonly used particle electrode in current research. Activated carbon has the advantages of high mechanical strength, large specific surface area, excellent adsorption performance, and long service life. Due to the low electron transfer ability and electrical reactivity of activated carbon particles, as particle electrodes in three-dimensional systems, their electrochemical oxidation ability is poor and short circuits are prone to occur. Therefore, how to develop high-performance, low-cost particle electrodes and realize the practical application of three-dimensional electrocatalysis in wastewater treatment remains a challenge.

[0004] In order to improve the catalytic performance of granular activated carbon, researchers coated metal (Fe, Cu, Zn, Ti, Sn, Ce, Ni) oxides on the granular electrodes as catalysts. In addition, the rare earth element Ce as a dopant has a high (Ce 3+ / Ce 4+ ) redox potential, and Ce and Sn, 2Ce 4+ +Sn 2+ →2Ce 2+ +Sn 4+ There is a synergistic effect between them, which can enhance the redox ability and improve the electrocatalytic ability of the electrocatalyst, thereby optimizing the electrocatalytic performance. Therefore, it is of great significance to use the advantages of carbon-based materials to develop transition metal and rare earth metal modified particle electrodes, increase the system's electron transfer capacity, and achieve efficient electrocatalytic oxidation in electrochemical treatment systems. Summary of the invention

[0005] The present invention provides a modified activated carbon granular electrode, preparation method and application for the high resistivity, strong adsorption, developed porosity and weak conductivity of granular activated carbon (GAC). The invention pre-treats the granular activated carbon and then uses the sol-gel method to dope the active components of Ce, Sn and Sb into the granular activated carbon to prepare a three-dimensional electrocatalytic modified particle electrode. The activity of the modified granular activated carbon electrode is significantly improved, thereby improving the degradation performance of refractory organic matter in wastewater and increasing the feasibility of engineering application of granular electrodes.

[0006] In a first aspect, the present invention provides a method for preparing a three-dimensional electrocatalytic modified particle electrode based on a sol-gel method, the preparation method comprising:

[0007] (1) pretreating coconut shell activated carbon particles to obtain pretreated coconut shell activated carbon particles;

[0008] (2) mixing tin chloride, antimony chloride, cerium nitrate, a hydrolysis polycondensation catalyst and a solvent to obtain a mixed solution;

[0009] (3) placing the pretreated coconut shell activated carbon particles in the mixed solution for heating treatment, taking them out, and sequentially drying and calcining them to obtain a three-dimensional electrocatalytic modified particle electrode.

[0010] Preferably, in step (1), the particle size of the coconut shell activated carbon particles is 8 to 10 meshes.

[0011] Preferably, in step (1): the pretreatment comprises water washing, alkali washing, water washing, acid washing, and water washing in sequence.

[0012] Preferably, in step (1), the alkaline washing is performed by using a sodium hydroxide aqueous solution with a concentration of 0.1 mol / L and washing for 30 minutes at the boiling point temperature of the sodium hydroxide aqueous solution.

[0013] Preferably, in step (1), the pickling is performed by using a hydrochloric acid aqueous solution with a concentration of 0.1 mol / L and washing for 30 minutes at the boiling point temperature of the hydrochloric acid aqueous solution.

[0014] Preferably, in step (2): the molar concentration ratio of tin chloride to antimony chloride in the mixed solution is 10:1.

[0015] Preferably, in step (2): the molar concentration ratio of tin chloride to cerium nitrate in the mixed solution is 50:(1-5).

[0016] Preferably, in step (2): the hydrolysis and polycondensation catalyst is hydrochloric acid; the solvent is ethanol; and the mixed solution comprises 100 mL of ethanol and 5 mL of 1 mol / L hydrochloric acid.

[0017] Preferably, in step (3): the heating treatment is heating at 70° C. for 4 hours.

[0018] Preferably, in step (3), the drying temperature is 90°C.

[0019] Preferably, in step (3), the calcination is carried out at 400-500° C. in an air atmosphere for 2-4 hours.

[0020] In a second aspect, the present invention further provides a three-dimensional electrocatalytic modified particle electrode prepared by any preparation method of the first aspect.

[0021] In a third aspect, the present invention further provides an application of the three-dimensional electrocatalytic modified particle electrode of the second aspect in degrading organic wastewater and high-salt organic wastewater.

[0022] Compared with the prior art, the present invention has at least the following beneficial effects:

[0023] (1) The present invention realizes transition metal and rare earth metal loaded granular activated carbon electrode by sol-gel method. The activity of the modified granular activated carbon electrode is significantly improved.

[0024] (2) The modified granular activated carbon electrode used in the present invention effectively enhances the ability of the active substances produced by the anode material, thereby improving the efficiency of treating difficult-to-degrade organic pollutants in wastewater and the efficiency of treating pollutants in high-salt wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0026] Figure 1 A SEM image of coconut shell activated carbon particles provided in an embodiment of the present invention at a magnification of 10K;

[0027] Figure 2 This is a SEM image of a three-dimensional electrocatalytic modified particle electrode provided in Example 2 of the present invention at a magnification of 10K;

[0028] Figure 3This is a SEM image of a three-dimensional electrocatalytic modified particle electrode provided in Example 2 of the present invention at a magnification of 20K;

[0029] Figure 4 This is an EDS spectrum diagram of a three-dimensional electrocatalytic modified particle electrode provided in Example 2 of the present invention;

[0030] Figure 5 An adsorption curve of a three-dimensional electrocatalytic modified particle electrode provided by an embodiment of the present invention. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0032] like Figure 1 As shown, an embodiment of the present invention provides a method for preparing a three-dimensional electrocatalytic modified particle electrode based on a sol-gel method, the preparation method comprising:

[0033] (1) pretreating coconut shell activated carbon particles to obtain pretreated coconut shell activated carbon particles;

[0034] (2) mixing tin chloride, antimony chloride, cerium nitrate, a hydrolysis polycondensation catalyst and a solvent to obtain a mixed solution;

[0035] (3) The pretreated coconut shell activated carbon particles are placed in a mixed solution for heating treatment, taken out, and dried and calcined in sequence to obtain a three-dimensional electrocatalytic modified particle electrode.

[0036] In the present invention, after the granular coconut shell activated carbon is pretreated, the active components of Ce, Sn and Sb are doped into the coconut shell activated carbon by a sol-gel method, and the modified coconut shell activated carbon, i.e., a three-dimensional electrocatalytic modified particle electrode, is obtained by calcination. In this way, since the active components are distributed in the coconut shell activated carbon, the activity of the coconut shell activated carbon is improved, the problem of high resistivity and weak conductivity of the coconut shell activated carbon is solved, and the degradation performance of the difficult-to-degrade organic matter in the wastewater is improved, and the feasibility of the engineering application of the granular electrode is increased.

[0037] According to some preferred embodiments, in step (1): the particle size of the coconut shell activated carbon particles is 8 to 10 meshes.

[0038] According to some preferred embodiments, in step (1): pretreatment comprises sequentially performing water washing, alkali washing, water washing, acid washing, and water washing.

[0039] According to some preferred embodiments, in step (1): alkaline washing is performed by using a sodium hydroxide aqueous solution with a concentration of 0.1 mol / L and washing for 30 minutes at the boiling point temperature of the sodium hydroxide aqueous solution.

[0040] According to some preferred embodiments, in step (1): the acid wash is performed using a hydrochloric acid aqueous solution with a concentration of 0.1 mol / L and washing at the boiling point temperature of the hydrochloric acid aqueous solution for 30 minutes.

[0041] Specifically, in step (1), the coconut shell activated carbon particles are first repeatedly rinsed with pure water until the filtrate is clear, and then the washed coconut shell activated carbon is boiled and washed with a 0.1 mol / L NaOH aqueous solution for 30 minutes, and then washed with pure water, and then boiled and washed with a 0.1 mol / L HCl aqueous solution for 30 minutes, and finally the acid-washed coconut shell activated carbon is rinsed with pure water until the filtrate is neutral, and then ultrasonically cleaned for 30 minutes to remove substances adsorbed on the surface of the coconut shell activated carbon particles and grease and impurities in their pores.

[0042] According to some preferred embodiments, in step (2): the molar concentration ratio of tin chloride to antimony chloride in the mixed solution is 10:1.

[0043] According to some preferred embodiments, in step (2): the molar concentration ratio of tin chloride to cerium nitrate in the mixed solution is 50:(1-5).

[0044] According to some preferred embodiments, in step (2): the hydrolysis polycondensation catalyst is hydrochloric acid; the solvent is ethanol; and the mixed solution includes 100 mL of ethanol and 5 mL of 1 mol / L hydrochloric acid.

[0045] According to some preferred embodiments, in step (3): the heating treatment is heating at 70° C. for 4 hours.

[0046] According to some preferred embodiments, in step (3): the drying temperature is 90°C.

[0047] According to some preferred embodiments, in step (3): calcination is carried out at 400-500° C. in an air atmosphere for 2-4 hours.

[0048] The present invention also provides a three-dimensional electrocatalytic modified particle electrode prepared by the above preparation method.

[0049] In the present invention, an organic glass container is used as a three-dimensional electrochemical reactor with an effective volume of 3 L. The anode of the DC power supply is a 10 cm×10 cm iridium ruthenium mesh electrode, the cathode is a 10 cm×10 cm titanium mesh electrode, the diamond hole size of the electrode is 5 mm×10 mm, the working area of ​​the electrode is 10 cm×10 cm, the distance between the anode and cathode plates is 5 cm, and a three-dimensional electrocatalytic modified particle electrode is filled between the two main electrodes to form a three-dimensional electrochemical system.

[0050] The present invention also provides an application of a three-dimensional electrocatalytic modified particle electrode in degrading organic wastewater and high-salt organic wastewater.

[0051] Unless otherwise specified, the raw materials used in the present invention can be products that can be directly purchased on the market or synthesized by existing methods.

[0052] In the present invention, “and / or” appearing between multiple technical features means that these technical features are connected in an “and / or” relationship, indicating that it can be any one of these technical features, or a combination of any two or more of these technical features.

[0053] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments.

[0054] Example 1: Preparation of granular activated carbon electrodes by doping with different active components

[0055] Methylisothiazolinone (MIT) is a commonly used non-oxidizing fungicide with toxic risks and is difficult to biodegrade. It has a significant adverse impact on the marine ecosystem after being discharged into the environment. Due to its difficulty in biodegradation, the biodegradation removal rate of MIT is low in conventional sewage treatment systems, so it is used as a target pollutant. The initial concentration of MIT solution is 50 mg / L, the electrolyte is 0.25 mol / L Na2SO4, and the current density is 15 mA / cm 2 The anode is a 10cm×10cm iridium ruthenium mesh electrode, the cathode is a 10cm×10cm titanium mesh electrode, and coconut shell activated carbon with no loading (GAC), loading tin and antimony (Sn-Sb / GAC), and loading tin, antimony, and cerium (Sn-Sb-Ce / GAC) is filled between the two main electrodes as a particle electrode for electrocatalytic oxidation testing. The target pollutants were treated under the same initial conditions, and the amount of particle electrodes was the same. The concentration of MIT was measured after 120 minutes of reaction degradation and compared with the two-dimensional electrode system.

[0056] After 120 minutes of electrocatalytic degradation, the removal rate of MIT in the two-dimensional electrode system was 68%. The removal rates of MIT in the three-dimensional electrode system with GAC, Sn-Sb / GAC, and Sn-Sb-Ce / GAC as particle electrodes were 89%, 92%, and 94%, respectively. The removal rate of the target pollutants increased by at least 20% with the addition of conductive particles, and the particle electrodes loaded with three active components of Sn, Sb, and Ce had the best treatment performance.

[0057] Example 2: Preparation of Sn-Sb-Ce / GAC

[0058] (1) Filter the coconut shell activated carbon particles to 8-10 mesh, rinse them repeatedly with pure water until the filtrate is clear, then boil and wash the washed coconut shell activated carbon with a 0.1 mol / L NaOH aqueous solution for 30 min, then wash it with pure water, then boil and wash the washed coconut shell activated carbon with a 0.1 mol / L HCl aqueous solution for 30 min, finally rinse the acid-washed coconut shell activated carbon with pure water until the filtrate is neutral, then use ultrasonic cleaning for 30 min, and dry it at 110° C. for 12 h to obtain pretreated coconut shell activated carbon particles;

[0059] (2) adding 5 mL of 1 mol / L hydrochloric acid aqueous solution, tin chloride SnCl4·5H2O, antimony chloride SbCl3, and cerium nitrate Ce(NO3)3·H2O to 100 mL of anhydrous ethanol and mixing the mixture to obtain a mixed solution; wherein the concentration of tin chloride in the mixed solution is 0.3 mol / L, the concentration of antimony chloride is 0.03 mol / L, and the concentration of cerium nitrate is 0.018 mol / L; the molar concentration ratio of tin chloride to antimony chloride is 10:1; and the molar concentration ratio of tin chloride to cerium nitrate is 50:3;

[0060] (3) The pretreated coconut shell activated carbon particles are placed in the mixed solution of step (2) and heated in a water bath at 70° C. with stirring for 4 h, then taken out and dried at 90° C., and finally calcined in an air atmosphere at 400° C. for 3 h to obtain a Sn-Sb-Ce / GAC three-dimensional electrocatalytic modified particle electrode.

[0061] From the scanning electron microscopy image of the three-dimensional electrocatalytic modified particle electrode ( Figures 1 to 3 ) It can be seen that the SEM images of activated carbon loaded with Sn, Sb, and Ce metals are significantly different. Figure 1 It can be seen that the surface of unloaded GAC is rough and has many voids. Figure 2 It can be clearly seen that the co-doping of the three components has a significant effect on the morphology of the electrode. The crystal particles are densely and evenly distributed on the electrode surface, which improves the roughness of the electrode. Figure 3It can be seen that compared with activated carbon, the surface of Sn-Sb-Ce / GAC material has many spherical, cylindrical and cubic crystals of different shapes. During the sol-gel treatment, the surface and inner wall of GAC were unevenly covered with Sn, Sb, and Ce catalysts, indicating that the three metals were loaded on the GAC particle electrode. This shows that the Sn-Sb-Ce / GAC material was successfully prepared.

[0062] From the element distribution of the sample EDS electrode surface ( Figure 4 ) It can be seen that the atomic percentage of Sn element is about 10.54%, the atomic percentage of Sb element is about 0.23%, and the atomic percentage of Ce element is about 0.75%, indicating that Sn, Sb, and Ce are loaded on the GAC particle electrode. This shows that the Sn-Sb-Ce / GAC material was successfully prepared.

[0063] The experiment was carried out at an initial MIT concentration of 50 mg / L, room temperature of 20 °C, and a current density of 20 mA / cm 2 , pH 5, electrolyte Na2SO4 concentration of 0.2 mol / L, Sn-Sb-Ce / GAC particle electrode dosage of 5 g / L. After one experiment, the particle electrode does not need to be separated and re-added to the MIT simulated water sample for the next experiment. As shown in Table 1, the recycling treatment efficiency of the particle electrode and the dissolution of active components, after 10 cycles, the system's removal rate of MIT decreased from 92.93% to 88.49%, but the removal rate of MIT did not decrease significantly. The low dissolution of Ce, Sn, and Sb ions ensures the long-term effectiveness of the catalytic oxidation ability of the particle electrode and will not cause secondary pollution to the water body. Therefore, the structural stability of the Sn-Sb-Ce / GAC particle electrode has a certain degree of durability and has potential for engineering application.

[0064] Table 1

[0065]

[0066]

[0067] It should be noted that ND in Table 1 means that the Ce elution amount was not detected.

[0068] Example 3: Preparation of Sn-Sb-Ce / GAC

[0069] (1) Filter the coconut shell activated carbon particles to 8-10 mesh, rinse them repeatedly with pure water until the filtrate is clear, then boil and wash the washed coconut shell activated carbon with a 0.1 mol / L NaOH aqueous solution for 30 min, then wash it with pure water, then boil and wash the washed coconut shell activated carbon with a 0.1 mol / L HCl aqueous solution for 30 min, finally rinse the acid-washed coconut shell activated carbon with pure water until the filtrate is neutral, then use ultrasonic cleaning for 30 min, and dry it at 110° C. for 12 h to obtain pretreated coconut shell activated carbon particles;

[0070] (2) adding 5 mL of 1 mol / L hydrochloric acid aqueous solution, tin chloride SnCl4·5H2O, antimony chloride SbCl3, and cerium nitrate Ce(NO3)3·H2O to 100 mL of anhydrous ethanol and mixing the mixture to obtain a mixed solution; wherein the concentration of tin chloride in the mixed solution is 0.1 mol / L, the concentration of antimony chloride is 0.01 mol / L, and the concentration of cerium nitrate is 0.002 mol / L; the molar concentration ratio of tin chloride to antimony chloride is 10:1; and the molar concentration ratio of tin chloride to cerium nitrate is 50:1;

[0071] (3) The pretreated coconut shell activated carbon particles are placed in the mixed solution of step (2) and heated in a water bath at 70° C. with stirring for 4 h, then taken out and dried at 90° C., and finally calcined in an air atmosphere at 400° C. for 2 h to obtain a Sn-Sb-Ce / GAC three-dimensional electrocatalytic modified particle electrode.

[0072] The initial concentration of MIT solution is 50mg / L water sample. The electrolyte is 0.25mol / LNa2SO4, and the current density is 15mA / cm 2 The anode was a 10 cm×10 cm iridium ruthenium mesh electrode, the cathode was a 10 cm×10 cm titanium mesh electrode, and the Sn-Sb-Ce / GAC particle electrode prepared in Example 3 was filled between the two main electrodes for electrocatalytic oxidation ability test. After 120 min of reaction degradation, the removal rate of MIT was determined to be 98.7%.

[0073] Example 4: Preparation of Sn-Sb-Ce / GAC

[0074] The preparation method of the three-dimensional electrocatalytic modified particle electrode of this embodiment is the same as that of embodiment 3, except that the molar ratio of Sn to Ce is changed to 50:3, the calcination temperature is changed to 450°C, and the calcination time is changed to 3 hours. After 120 minutes of reaction degradation, the removal rate of MIT is measured to be 92.6%.

[0075] Example 5: Preparation of Sn-Sb-Ce / GAC

[0076] The preparation method of the three-dimensional electrocatalytic modified particle electrode of this embodiment is the same as that of embodiment 4, except that the molar ratio of Sn to Ce is changed to 50:5, the calcination temperature is changed to 500° C., and the calcination time is changed to 4 h. After 120 min of reaction degradation, the removal rate of MIT is measured to be 87.9%.

[0077] Example 6: Preparation of Sn-Sb-Ce / GAC

[0078] The preparation method of the three-dimensional electrocatalytic modified particle electrode of this embodiment is the same as that of Example 5, except that the concentration of SnCl4·5H2O is changed to 0.3 mol / L, the molar ratio of Sn to Ce is changed to 50:1, the calcination temperature is changed to 450°C, and the calcination time is changed to 3 hours. After 120 minutes of reaction degradation, the removal rate of MIT is measured to be 88.5%.

[0079] Example 7: Preparation of Sn-Sb-Ce / GAC

[0080] The preparation method of the three-dimensional electrocatalytic modified particle electrode of this embodiment is the same as that of Example 6, except that the molar ratio of Sn to Ce is changed to 50:3, the calcination temperature is changed to 500° C., and the calcination time is changed to 2 h. After 120 min of reaction degradation, the removal rate of MIT is measured to be 94.8%.

[0081] Example 8: Preparation of Sn-Sb-Ce / GAC

[0082] The preparation method of the three-dimensional electrocatalytic modified particle electrode of this embodiment is the same as that of Example 7, except that the molar ratio of Sn to Ce is changed to 50:5, the calcination temperature is changed to 400° C., and the calcination time is changed to 3 h. After 120 min of reaction degradation, the removal rate of MIT is measured to be 96.2%.

[0083] Example 9: Preparation of Sn-Sb-Ce / GAC

[0084] The preparation method of the three-dimensional electrocatalytic modified particle electrode of this embodiment is the same as that of Example 8, except that the concentration of SnCl4·5H2O is changed to 0.5 mol / L, the molar ratio of Sn to Ce is changed to 50:1, and the calcination temperature is changed to 500° C. After 120 min of reaction degradation, the removal rate of MIT is measured to be 90.3%.

[0085] Example 10: Preparation of Sn-Sb-Ce / GAC

[0086] The preparation method of the three-dimensional electrocatalytic modified particle electrode of this embodiment is the same as that of embodiment 9, except that the molar ratio of Sn to Ce is changed to 50:3, the calcination temperature is changed to 400° C., and the calcination time is changed to 4 h. After 120 min of reaction degradation, the removal rate of MIT is measured to be 95.7%.

[0087] Example 11: Preparation of Sn-Sb-Ce / GAC

[0088] The preparation method of the three-dimensional electrocatalytic modified particle electrode of this embodiment is the same as that of embodiment 10, except that the molar ratio of Sn to Ce is changed to 50:5, the calcination temperature is changed to 450°C, and the calcination time is changed to 2 hours. After 120 minutes of reaction degradation, the removal rate of MIT is measured to be 85.0%.

[0089] The removal rates of MIT by the three-dimensional electrocatalytic modified particle electrodes prepared in Examples 3 to 11 are shown in Table 2.

[0090] Table 2

[0091]

[0092] As shown in Table 2, the preparation method of the three-dimensional electrocatalytic modified particle electrode provided by the present invention can effectively treat wastewater containing MIT, a difficult-to-degrade organic matter. The present invention has the advantages of good stability and high electrocatalytic performance, and has good application prospects.

[0093] Example 12: Adsorption of Sn-Sb-Ce / GAC particle electrodes

[0094] The adsorption experiment was carried out at an initial MIT concentration of 250 mg / L, room temperature of 20 °C, and a current density of 20 mA / cm 2 , pH 5, electrolyte Na2SO4 concentration 0.2mol / L. First, three-dimensional electrocatalytic modified particle electrodes of different masses (5g, 10g, 20g, 40g, 70g) were immersed in a 250mg / L MIT solution and placed under a magnetic stirrer to disperse the particle electrodes evenly. Then, static adsorption was performed for 24h, and samples were taken at regular intervals to measure the MIT concentration. Figure 5 It can be seen that the adsorption amount of the three-dimensional electrocatalytic modified particle electrode decreases with the increase of the particle electrode dosage. When the particle electrode dosage is 5 g / L, the adsorption amount of the particle electrode is the largest.

[0095] Example 13: Effect of Sn-Sb-Ce / GAC particle electrode on the removal of pollutants in actual water samples

[0096] MIT and salt were added to the secondary effluent of a municipal sewage treatment plant to prepare high-salt organic wastewater as experimental water. - The concentration is 6630mg / L, SO4 2- The concentration is 12950 mg / L. The initial MIT concentration in the electrocatalytic oxidation device is 50 mg / L, the room temperature is 20 °C, and the current density is 20 mA / cm 2, pH is 5, electrolyte Na2SO4 concentration is 0.2 mol / L. The anode is a 10cm×10cm iridium ruthenium mesh electrode, the cathode is a 10cm×10cm titanium mesh electrode, and 5 g / L of Sn-Sb-Ce / GAC particle electrode prepared in Example 2 is filled between the two main electrodes for electrocatalytic oxidation ability test.

[0097] After 30 min of reaction, the removal rate of MIT by the three-dimensional electrochemical system can reach 96.5%, which may be due to the large amount of Cl- and SO4 in the secondary effluent. 2- , can produce chlorine free radicals, ·OH, ·SO4 under electrocatalysis 2- , so the degradation efficiency is high. After 120 minutes of reaction, the removal rates of COD and TOC by the three-dimensional electrochemical system were 42.6% and 13.7%, respectively, indicating that the system has a certain degradation ability for organic matter in high-salinity organic wastewater, but it is difficult to completely mineralize and remove pollutants.

[0098] Therefore, the modified Sn-Sb-Ce / GAC three-dimensional electrocatalytic modified particle electrode not only has significantly improved electrocatalytic oxidation ability, but also has excellent stability, and has high application value in the field of actual wastewater treatment.

[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them; although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present invention. The parts not described in detail in the present invention are well-known technologies of those skilled in the art.

Claims

1. A method for preparing a three-dimensional electrocatalytic modified particle electrode based on a sol-gel method, characterized in that: include: (1) pretreating coconut shell activated carbon particles to obtain pretreated coconut shell activated carbon particles; (2) mixing tin chloride, antimony chloride, cerium nitrate, a hydrolysis polycondensation catalyst and a solvent to obtain a mixed solution; (3) placing the pretreated coconut shell activated carbon particles in the mixed solution for heating treatment, taking them out, and sequentially drying and calcining them to obtain a three-dimensional electrocatalytic modified particle electrode.

2. The preparation method according to claim 1, characterized in that: In step (1): The particle size of the coconut shell activated carbon particles is 8 to 10 meshes.

3. The preparation method according to claim 1, characterized in that: In step (1): The pretreatment includes water washing, alkali washing, water washing, acid washing and water washing in sequence.

4. The preparation method according to claim 3, characterized in that: In step (1): The alkaline washing is performed by using a sodium hydroxide aqueous solution with a concentration of 0.1 mol / L and washing for 30 minutes at the boiling point temperature of the sodium hydroxide aqueous solution; and / or, The acid washing is performed by using a hydrochloric acid aqueous solution with a concentration of 0.1 mol / L and washing for 30 minutes at the boiling point temperature of the hydrochloric acid aqueous solution.

5. The preparation method according to claim 1, characterized in that: In step (2): The molar concentration ratio of tin chloride to antimony chloride in the mixed solution is 10:1; and / or, The molar concentration ratio of tin chloride to cerium nitrate in the mixed solution is 50:(1-5).

6. The preparation method according to claim 1, characterized in that: In step (2): The hydrolysis and polycondensation catalyst is hydrochloric acid; the solvent is ethanol; The mixed solution includes 100 mL of ethanol and 5 mL of 1 mol / L hydrochloric acid.

7. The preparation method according to claim 1, characterized in that: In step (3): The heating treatment is heating at 70° C. for 4 hours; and / or, The drying temperature is 90°C.

8. The preparation method according to any one of claims 1 to 7, characterized in that: In step (3): The calcination is carried out at 400-500° C. in an air atmosphere for 2-4 hours.

9. A three-dimensional electrocatalytic modified particle electrode prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the three-dimensional electrocatalytic modified particle electrode according to claim 9 in degrading organic wastewater and high-salt organic wastewater.

Citation Information

Patent Citations

  • Method for treating desulfurization wastewater by using modified activated carbon particle electrode

    CN109694119A

  • Electrochemically modified filler for water treatment

    CN110282704A

  • Three-dimensional particle electrode for wastewater treatment and preparation method thereof

    CN114409028A

  • Preparation method and application of tin and antimony loaded modified activated carbon particle electrode

    CN115893594A

  • KR20240163638A

Cited By

  • Method and device for synergistically treating new pollutants through multi-source catalysis coupling adsorption

    CN120757205A